Analytical and experimental evaluation of SiC-inverter nonlinearites for traction drives used in electric vehicles - Ding, Xiaofeng; Du, Min; Duan, Chongwei; Guo, Hong; Xiong, Rui; Xu, Jinquan; Cheng, Jiawei; Luk, Patrick Chi-Kwong (IEEE, 2017)
This paper investigates the inverter nonlinearities in a drive system based on silicon carbide metal-oxide-semiconductor field-effect transistor (SiC-mosfets) and compares its performance with that of an equivalent silicon insulated-gate bipolar transistor (Si-IGBT) system. Initially, a novel comprehensive analytical model of the inverter voltage distortion is developed. Not only voltage drops, dead time, and output capacitance, but also switching delay times and voltage overshoot of the power devices are taken into account in the model. Such a model yields a more accurate prediction of the inverter's output voltage distortion, and is validated by experimentation. Due to inherent shortcomings of the commonly used double pulse test, the switching characteristics of both SiC-mosfets and Si-IGBTs in the pulse width modulation inverter are tested instead, such that the actual performances of the SiC and Si devices in the motor drive system are examined. Then, the switching performance is incorporated into the physical model to quantify the distorted voltages of both the SiC-based and Si-based systems. The results show that, despite its existing nonlinearities, the SiC-based drive has lower voltage distortion compared to the conventional Si-based drive as a result of its shorter switching times and smaller voltage drop, as well as a higher efficiency. Finally, the overriding operational advantages of the SiC-based drive over its Si-based counterpart is fully demonstrated by comprehensive performance comparisons.
Keywords: Efficiency; Electric vehicles (EVs); Inverter nonlinearity; Silicon (Si); Silicon carbide (SiC); Voltage distortion